2018
DOI: 10.1136/jnnp-2018-318470
|View full text |Cite
|
Sign up to set email alerts
|

Apraxia screening predicts Alzheimer pathology in frontotemporal dementia

Abstract: ObjectivesFrontotemporal dementia (FTD) is a heterogeneous clinical syndrome linked to diverse types of underlying neuropathology. Diagnosis is mainly based on clinical presentation and accurate prediction of underlying neuropathology remains difficult.MethodsWe present a large cohort of patients with FTD spectrum diseases (n=84). All patients were thoroughly characterised by cerebrospinal fluid (CSF) Alzheimer’s disease (AD) biomarkers, neuroimaging, neuropsychological testing and standardised apraxia screeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The systematic literature search yielded 1257 records, of which 116 studies were assessed at full-text level for eligibility and 83 studies met inclusion criteria (eFigure 5 in the Supplement for flowchart). Confirmation of AD pathology was present in 91.1% of cases with bvAD based on autopsy data (36 studies; n = 334), genetic data (9 studies; n = 21), or biomarker data (31 studies; n = 262), while no information was available in 9.9% of cases (11 studies including 68 cases of bvAD). Thirteen studies were eligible for meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The systematic literature search yielded 1257 records, of which 116 studies were assessed at full-text level for eligibility and 83 studies met inclusion criteria (eFigure 5 in the Supplement for flowchart). Confirmation of AD pathology was present in 91.1% of cases with bvAD based on autopsy data (36 studies; n = 334), genetic data (9 studies; n = 21), or biomarker data (31 studies; n = 262), while no information was available in 9.9% of cases (11 studies including 68 cases of bvAD). Thirteen studies were eligible for meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…These features were seen in both patients with AD pathology and the majority of those with FTLD. Apraxia has been reported more frequently in typical AD with positive biomarkers [31,32] but was not present at initial assessment in either of our cases of bvFTD with AD pathology. Previous studies suggest that apathy is non-specific in neurodegenerative diseases [4,9,32] and it was present in both AD and FTLD patients in the present study.…”
Section: Discussionmentioning
confidence: 45%
“…Recent research has demonstrated that apraxia screening can also predict dementia disease progression (Pawlowski et al, 2019), especially as a way to predict AD in early stage FTD subjects, a population that we are particularly interested in targeting with our biomarkers. For the Behavioral Variant of Fronto Temporal Dementia (bvFTD), in patients under 65 the second most common cognitive disorder caused by neurodegeneration, little tonal modulation and buccofacial apraxia, are targeted by our biomarkers and are established diagnostic domains (Johnen and Bertoux, 2019).…”
Section: Respiratory Tract Biomarkers Cough and Wake Wordmentioning
confidence: 99%